Core concepts in health : - Insel, Paul M. (McGraw-Hill, 2002)
The most reliable and widely used personal health text, Core Concepts in Health utilizes the theme of personal responsibility to teach and motivate students about health and wellness. The ninth Edition Update provides current, accurate, scientifically based information about a wealth of health and wellness topics and issues. The Brief edition, an affordable alternative to larger health texts, includes a built-in study guide that allows students to test their knowledge of health-related issues and assess their level of wellness.